Learning disabilities identification, assessment, and instruction of students with LD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2013)
This volume addresses the most current perspectives and issues related to learning disabilities and is written by leaders in the field of learning disabilities. The layout of the book and ordering of chapters will allow readers to follow learning disabilities in a very logical and thoughtful process from legal issues, identification, and assessment, to effective practices and response to intervention finally ending with practical issues of inclusion, working with families, and teacher preparation. Chapters can be read in order or independently which will allow readers considerable versatility. Chapters in the book include: Legal Issues and Learning Disabilities; Themes and Dimensions of Learning Disabilities; Identification and Assessment of Students with LD; Placement of Students with Learning Disabilities; Culturally and Linguistically Diverse Students who have Learning Disabilities; Prevention Strategies for At-Risk Students with Learning Disabilities; ELL Students and Learning Disabilities; Differentiating Instruction and Students with Learning Disabilities; Interventions for CLD Learners with Learning Disabilities; Positive Behavior Supports and Students with Learning Disabilities.
Legal issues and students with learning disabilities / Mitchell L. Yell, Todd W. Busch -- Themes and dimensions of learning disabilities / Valerie L. Mazzotti, April L. Mustian -- Assessment and LD : determining eligibility, selecting services, and guiding instruction / Frederick J. Brigham, Jeffrey P. Bakken -- Placement of students with learning disabilities / Cynthia G. Simpson, Chad A. Rose, Jeffrey P. Bakken -- Culturally and linguistically diverse students labeled as having learning disabilities / Yvel C. Crevecoeur, Festus E. Obiakor -- Prevention strategies for students at-risk for learning disabilities / Amina M. Turton, Satasha Green -- Evaluating bilingual students for learning disabilities / Beatriz A. Duarte, Barbara Greybeck, Cynthia G. Simpson -- English language learners and learning disabilities / Amy Eppolito, Cristin Jensen Lasser, Janette Klingner -- Differentiated instruction and students with learning disabilities / Lenwood Gibson -- Reframing outcomes for students with learning disabilities : the application of a problem-solving approach / Michelle Marchant, Gordon S. Gibb, Darlene Anderson.
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Special Education -- General; Education -- Evaluation; Teaching of specific groups & persons with special educational needs; Teaching of students with emotional & behavioural difficulties; Learning disabilities